Gastrointestinal surgical techniques in small animals - Monnet, Eric; Smeak, Daniel D. (Hoboken, NJ : Wiley Blackwell, 2020)
"Gastrointestinal Surgical Techniques in Small Animals offers a highly detailed reference to surgical procedures in the gastrointestinal tract in dogs and cats. Each chapter describes the surgical techniques in depth, featuring high-quality illustrations depicting each step, and discusses tips and tricks for a successful surgery and potential complications. A companion website offers video clips demonstrating the procedures. Logically divided into sections by anatomy, each chapter covers indications, contraindications, and decision making for a specific surgery. Tips and tricks and potential complications are also covered. Gastrointestinal Surgical Techniques in Small Animals is an essential resource for small animal surgeons and veterinary residents"--
Intestinal healing / Eric Monnet and Daniel Smeak -- Suture materials, staplers, and tissue apposition devices / Daniel Smeak -- Suture pattern / Daniel Smeak -- Feeding tubes / Eric Monnet -- Drainage technique / Eric Monnet -- Mandibulectomy and maxillectomy / Bernard Seguin -- Glossectomy / Eric Monnet and Bernard Seguin -- Tonsillectomy / Eric Monnet and Bernard Seguin -- Palate defect / Chad Lothamer and Jennifer Rawlinson -- Salivary glands surgery / Daniel Smeak -- Esophagotomy / Eric Monnet -- Esophagectomy / Eric Monnet -- Cricopharyngeal myectomy and Heller myectomy / Eric Monnet -- Vascular ring anomalies / Eric Monnet -- Hiatal hernia / Eric Monnet -- Anatomy and physiology of the stomach / Eric Monnet -- Gastrotomy / Eric Monnet -- Gastrectomy / Eric Monnet -- Billroth I / Eric Monnet -- Billroth II / Eric Monnet -- Pyloroplasty / Eric Monnet -- Roux in Y / Eric Monnet -- Gastropexy / Daniel Smeak -- Enterotomy / Daniel Smeak -- Enterectomy / Daniel Smeak -- Enteroplication / Daniel Smeak -- Colectomy / Daniel Smeak and Eric Monnet -- Colotomy / Daniel Smeak -- Thyplectomy / Daniel Smeak -- Colostomy / Daniel Smeak -- Colopexy / Daniel Smeak -- Approaches to the rectum / Daniel Smeak -- Surgery of the rectum / Daniel Smeak -- Anal sac resection / Daniel Smeak -- Liver lobectomy / Eric Monnet -- Surgery of the gall bladder / Eric Monnet -- Biliary diversion / Eric Monnet -- Surgery of the bile duct / Eric Monnet -- Biliary stenting / Eric Monnet -- Arterio-venous fistula / Eric Monnet -- Portosystemic shunts / Eric Monnet -- Surgery of the pancreas / Daniel Smeak.
Includes bibliographical references and index.
Keywords: Veterinary surgery; Gastrointestinal system -- Surgery; Pet medicine; Gastrointestinal system -- Diseases -- Treatment; Dogs -- Surgery; Cats -- Surgery; Veterinary surgery -- methods